2009
DOI: 10.5194/angeo-27-1969-2009
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the magnetic energy inside traveling compression regions

Abstract: Abstract. We investigate a series of six TCRs (traveling compression regions), appearing in the course of a small substorm on 19 September 2001. Except for two of these TCRs, all Cluster spacecraft were located in the lobe and detected the typical signatures of TCRs, i.e., compressions in |B| and bipolar B z variations. We use these perturbations in B z for calculations on the magnetic energy inside the TCR and compare the amount of magnetic field energy with the kinetic energy inside the underlying plasma bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…2003b; Kiehas et al, 2009aKiehas et al, , 2012. In a statistical study of TCRs observed with Cluster, Slavin et al [2005] found that in 76% of the observed events, TCRs occurred in series within a maximum interval of 15 min with the majority of these events being paired TCRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2003b; Kiehas et al, 2009aKiehas et al, , 2012. In a statistical study of TCRs observed with Cluster, Slavin et al [2005] found that in 76% of the observed events, TCRs occurred in series within a maximum interval of 15 min with the majority of these events being paired TCRs.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically, the relation of flux ropes and TCRs is shown in Slavin et al [], where Geotail observations of flux ropes are compared with TCR observations of Cluster. Event studies with Cluster and Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) show the direct relation between TCRs and flux ropes, when the flux rope and the associated TCR are simultaneously observed by spatially separated spacecraft [e.g., Slavin et al , ; Kiehas et al , , ]. In a statistical study of TCRs observed with Cluster, Slavin et al [] found that in 76% of the observed events, TCRs occurred in series within a maximum interval of 15 min with the majority of these events being paired TCRs.…”
Section: Introductionmentioning
confidence: 99%